Effect of cadmium chloride on the cardiac muscle ultrastructure of rats (International Journal of Biology and Chemistry, 2026)
Cadmium is a heavy metal and environmental pollutant that plays a significant role in the development of cardiovascular diseases. Chronic exposure to low concentrations of cadmium in experimental animals leads to various biochemical and pathophysiological changes, such as increased blood pressure, accelerated formation of cholesterol plaques in arterial walls, conduction disturbances in the heart, and reduced contractile function of the myocardium. This study aimed to evaluate ultrastructural changes in the heart muscle of rats poisoned with cadmium chloride, as well as to determine the extent of recovery of these changes after cadmium exposure was discontinued. Wistar rats weighing 180 – 200 grams were administered cadmium chloride orally at a dose of 1.5 mg/kg daily. The poisoning lasted for 10 weeks. After the cadmium administration was stopped, heart tissue samples were collected on the first day, one week, and two weeks later for analysis. Following cadmium administration, ultrastructural examination of the cardiac muscle fibers revealed an increased number of mitochondria with significant cristae damage. The number of myofibrils and myofilaments was reduced. Z-discs were partially displaced, and A and I bands were poorly distinguishable. Intercalated discs were irregularly positioned, and the sarcolemma was damaged. Two weeks after cadmium withdrawal, these structural changes were partially reduced. Thus, exposure to cadmium chloride is associated with ultrastructural alterations in the heart that may underline physiological dysfunctions, and it is suggested that these changes are partially reversible after the cessation of cadmium exposure.Key words: cadmium chloride, cardiac muscle, ultrastructure, myofibrils, myofilaments, rat.